Postoperative Outcomes Associated With Procedural Sedation Conducted by Physician and Nonphysician Anesthesia Providers: Findings From the Prospective, Observational African Surgical Outcomes Study. (28th December 2021) - van der Merwe, Freliza; Vickery, Nicola J.; Kluyts, Hyla-Louise; Yang, Dongsheng; Han, Yanyan; Munlemvo, Dolly M.; Ashebir, Daniel Z.; Mbwele, Bernard; Forget, Patrice; Basenero, Apollo; Youssouf, Coulibaly; Antwi-Kusi, Akwasi; et al.
Abstract : BACKGROUND: There is an unmet need for essential surgical services in Africa. Limited anesthesia services are a contributing factor. Nonphysician anesthesia providers are utilized to assist with providing anesthesia and procedural sedation to make essential surgeries available. There is a paucity of data on outcomes following procedural sedation for surgery in Africa. We investigated the postoperative outcomes following procedural sedation by nonphysicians and physicians in Africa. We hypothesized that the level of training of the sedation provider may be associated with the incidence of severe postoperative complications and death. METHODS: A secondary analysis of a prospective cohort of inhospital adult surgical patients representing 25 African countries was performed. The primary outcome was a collapsed composite of inhospital severe postoperative complications and death. We assessed the association between receiving procedural sedation conducted by a nonphysician (versus physician) and the composite outcome using logistic regression. We used the inverse probability of treatment weighting propensity score method to adjust for potential confounding variables including patient age, hemoglobin level, American Society of Anesthesiologists (ASA) physiological status, diabetes mellitus, urgency of surgery, severity of surgery, indication for surgery, surgical discipline, seniority of the surgical team, hospital level of specialization, and hospital funding system using public or private funding. All patients who only received procedural sedation for surgery were included. RESULTS: Three hundred thirty-six patients met the inclusion criteria, of which 98 (29.2%) received sedation from a nonphysician provider. The incidence of severe postoperative complications and death was 10 of 98 (10.2%) in the nonphysician group and 5 of 238 (2.1%) in the physician group. The estimated association between procedural sedation conducted by a nonphysician provider and inhospital outcomes was an 8-fold increase in the odds of severe complications and/or death, with an odds ratio (95% confidence interval [CI]) of 8.3 (2.7–25.6). CONCLUSIONS: The modest number of observations in this secondary data analysis suggests that shifting the task of procedural sedation from physicians to nonphysicians to increase access to care may be associated with severe postoperative complications and death in Africa. Research focusing on identifying factors contributing to adverse outcomes associated with procedural sedation is necessary to make this practice safer.